Economic evaluation of linaclotide for the treatment of adult patients with irritable bowel syndrome with constipation in the United States. (April 2015) - Huang, Huan; Taylor, Douglas C. A.; Carson, Robyn T.; Sarocco, Phil; Friedman, Mark; Munsell, Michael; Blum, Steven I.; Menzin, Joseph
Abstract Objectives: To use techniques of decision-analytic modeling to evaluate the effectiveness and costs of linaclotide vs lubiprostone in the treatment of adult patients with irritable bowel syndrome with constipation (IBS-C). Methods: Using model inputs derived from published literature, linaclotide Phase III trial data and a physician survey, a decision-tree model was constructed. Response to therapy was defined as (1) a ≥14-point increase from baseline in IBS-Quality-of-Life (IBS-QoL) questionnaire overall score at week 12 or (2) one of the top two responses (moderately/significantly relieved) on a 7-point IBS symptom relief question in ≥2 of 3 months. Patients who do not respond to therapy are assumed to fail therapy and accrue costs associated with a treatment failure. Model time horizon is aligned with clinical trial duration of 12 weeks. Model outputs include number of responders, quality-adjusted life-years (QALYs), and total costs (including direct and indirect). Both one-way and probabilistic sensitivity analyses were conducted. Results: Treatment for IBS-C with linaclotide produced more responders than lubiprostone for both response definitions (19.3% vs 13.0% and 61.8% vs 57.2% for IBS-QoL and symptom relief, respectively), lower per-patient costs (803 vs 911 and 977 vs 1056), and higher QALYs (0.1921 vs 0.1917 and 0.1909 vs 0.1894) over the 12-week time horizon. Results were similar for most one-way sensitivity analyses. In probabilistic sensitivity analyses, the majority of simulations resulted in linaclotide having higher treatment response rates and lower per-patient costs. Limitations: There are no available head-to-head trials that compare linaclotide with lubiprostone; therefore, placebo-adjusted estimates of relative efficacy were derived for model inputs. The time horizon for this model is relatively short, as it was limited to the duration of available clinical trial data. Conclusions: Linaclotide was found to be a less costly option vs lubiprostone for the treatment of adult patients with IBS-C.